Toward an Intercultural Higher Education: Questions for Rethinking Universities in Light of Contributions by Raúl Fornet-Betancourt - Acuña Rodríguez, María del Carmen (2026)
This essay arises from two rationales that include reflecting on the challenges that interculturality poses for universities and their institutional practices, and the experience of population groups that have been historically excluded from society and, consequently, from academia as an institution. In other words, the aim of this essay is to propose questions for (re)thinking universities—questions that may serve as a tool for institutional self-analysis, without functioning as an evaluative model, but rather as both a challenge and an opportunity for opening new possibilities for university practice. The study is organized into three sections. As a preamble, it offers reflections on higher education and interculturality. It then develops its central proposal based on Raúl Fornet-Betancourt’s (2006) “Eleven Provisional Theses for the Improvement of Interculturality Theories and Practices"” are reformulated as questions for higher education, particularly for public universities. These questions constitute a framework for critically approaching universities from an intercultural perspective. The study suggests that universities should consider these questions, with the hope that they may support their movement toward interculturality.